Vocal Music Therapy for Chronic Pain: A Mixed Methods Feasibility Study - Low, Ming Yuan; Lacson, Clarissa; Zhang, Fengqing; Kesslick, Amy; Bradt, Joke (The journal of alternative and complementary medicine (New York, N.Y.), 2020)
Objective: The purpose of this study was to determine the feasibility and preliminary effects of a vocal music therapy (VMT) program on chronic pain management. Design: A mixed methods intervention design was used in which qualitative data were embedded within a randomized controlled trial. Setting: An urban nurse-management health center on the East Coast of the United States. Subjects: Participants ( N = 43) were predominantly Black (79%) and female (76.7%) with an average pain duration of 10 years. Intervention: Participants were randomly allocated to a 12-week VMT program or a waitlist control. Outcome measures: We tracked consent rate (percentage of participants enrolled out of total number screened), attrition rate, and treatment adherence. We used PROMIS ® (Patient Reported Outcomes Measurement Information System) tools to measure pain interference, pain-related self-efficacy, pain intensity, depression, anxiety, positive effect, and well-being, ability to participate in social activities, and satisfaction with social roles at baseline and week 12. VMT participants also completed the Patient Global Impression of Change Scale. We conducted semistructured interviews to better understand participants' experience of the intervention. Results: The consent rate was 56%. The attrition rate was 23%. Large treatment effects (partial eta squared) were obtained for self-efficacy (0.20), depression (0.26), and ability to participate in social activities (0.24). Medium effects were found for pain intensity (0.10), anxiety (0.06), positive effect, and well-being (0.06), and small effects for pain interference (0.03) and satisfaction with social roles (0.03). On average, participants felt moderately better after completion of the VMT program ( M = 4.93, standard deviation = 1.98). Qualitative findings suggest that VMT resulted in better self-management of pain, enhanced psychological well-being, and stronger social and spiritual connections. Conclusions: Recruitment into the 12-week program was challenging, but quantitative and qualitative findings suggest significant benefits of VMT for chronic pain management.